HISTOPATHOLOGICAL PICTURE OF THE PANCREAS OF MICE (MUS MUSCULUS) DIABETES INDUCED BY STREPTOZOTOCIN-SUKROSA BY GIVING PEPAYA SEED EXTRACT (CARICA PAPAYA L.) - Fransiska Sitompul; Chatrine Angelica Dwi Christy; Yulvian Sani; Abraham Simatupang (International Journal Labs, 2024)
This study aimed to investigate the potential of papaya seed extract as an antihyperglycemic agent and to determine the histopathological features of the pancreas of female mice induced by streptozotocin-sucrose. The study used female DDY mice and divided them into five groups, including a negative control group, a positive control group, and three test groups given different doses of papaya seed methanol extract. The parameters measured were the decrease in fasting blood glucose levels, the number, diameter, and area of the islets of Langerhans in each group. The data was analyzed using the one-way ANOVA method with a confidence level of 95% followed by a comparison test using the Least Significant Difference method. The results showed that the methanol extract of papaya seeds has the potential to reduce blood glucose levels and improve the histological structure of the pancreas of diabetic mice induced by streptozotocin-sucrose at an optimum dose of 100 mg/kgBW. There was a significant difference in reducing blood glucose levels between the negative control group and the test group given 100 mg/kgBW papaya seed methanol extract after seven days of treatment. After fourteen days, there was a significant difference between the negative control group and test groups I, II, and III. Although no significant differences were found in the number, diameter, and area of the islets of Langerhans through morphometric photo testing, microscopic photo testing showed that test group I had the best histopathological picture with no vacuolization and necrosis found.